PERSEPSI MASYARAKAT NELAYAN DI DESA SWARANGAN TERHADAP PENDIDIKAN FORMAL - Abdul Aziz, Hamid; Wisnu Subroto; Fitri Mardiani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the complexity of educational challenges in Swarangan, a coastal village with 230 fishing households and 47 fishermen. Employing a qualitative approach through field observations and in-depth interviews, the research uncovers factors influencing low adolescent educational participation. Key findings reveal that infrastructure limitations, a 12-kilometer distance to the nearest high school, and poor road conditions significantly diminish motivation to continue education. A socioeconomic disparity is identified between prosperous seafood processors and economically constrained fishermen. The educational system faces structural challenges, with all educators originating from outside the village and an absenteeism rate 15% higher compared to schools with better infrastructure access. Adolescents tend to choose working as fishermen, with potential monthly earnings of 3-4 million rupiah. The research recommends a comprehensive approach through infrastructure improvement, strengthening teacher incentives, developing alternative economic empowerment programs, and initiating community-based education to create an inclusive educational ecosystem in coastal villages.